Antiphospholipid Immunoreactivity and TIAs - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
Clinical features that may predict the presence of antiphospholipid antibodies (aPL) in young patients with transient focal neurological events were determined in a study at the Henry Ford Hospital, Detroit, MI.